Eficiência simbiótica de estirpes de bactérias fixadoras de nitrogênio de diferentes procedências em caupi [Vigna unguiculata (L.) WALP.] e sua identificação. - Soares, Bruno Lima (2009)
The cowpea (Vigna unguiculata) is an important crop in the North and Northwest regions of Brazil because it is a source of protein and carbohydrates for low-income populations that cultivate and use it as food. However, this crop also has a great potential to be consumed in other regions of Brazil. The symbiosis between cowpea and nitrogen-fixing bacteria is extremely important to reduce costs and environmental impacts associated to fertilizer application. Our work aimed to evaluate the symbiotic efficiency of nitrogen-fixing bacterial strains isolated from the Amazon and bauxite mining sites, and to identify those strains by sequencing of their 16S rRNA gene. The symbiotic efficiency of twenty-eight strains isolated from different land use systems were tested and compared to strains currently recommended for cowpea inoculation, as well as to controls without inoculation, without nitrogen and with mineral nitrogen. Eight strains were selected based on their ability to increase the shoot dry matter when cowpea was cultivated in recipient containing soil. The strains UFLA3-164, UFLA3-153 and UFLA3-154 induced the highest increments in dry shoot matter. The soil used for the experiment presented high density of rhizobia with potential for nitrogen fixation. We verified that one of the three selected strains belongs to the genus Bradyrhizobium (UFLA 3-164) and another to the genus Burkholderia (UFLA-154).